Effect of new-style anterior and posterior vaginal wall repair combined with modified ischial spine fascia fixation on patients with pelvic organ prolapse and their postoperative quality of life - Wang, Gensheng; Zhou, Shengju; Wang, Shuhua; Xu, Dongdi; Wang, Dan; Xu, Hongling; Gao, Chuanlong; Li, Qing (Frontiers in Surgery, 2022)
Objective This study aims to explore the effect of new-style anterior and posterior vaginal wall repair combined with modified ischial spine fascia fixation on patients with pelvic organ prolapse (POP) and their postoperative quality of life. Methods A total of 88 patients with POP and elective surgery admitted to Anqing Hospital affiliated to Anhui Medical University from March 2018 to March 2021 were retrospectively analyzed. According to their surgical methods, patients were divided into an observation group [44 cases, all underwent new-style anterior and posterior vaginal wall repair combined with modified ischial spine fascia fixation (new-style APVR-modified ISFF)] and a control group [44 cases, all underwent traditional anterior and posterior vaginal wall repair combined with sacrospinous ligament fixation (traditional APVR- SLF)]. The perioperative indicators were compared between the two groups. The pelvic floor function, pelvic organ prolapse quantification (POP-Q) classification, and quality of life were observed before operation, 3 months after operation, and 6 months after operation. All patients were followed-up. Results Compared with the control group, the observation group had more advantages in intraoperative blood loss, operation time, urinary catheter indwelling time, postoperative anal exhaust time, and hospitalization time (P < 0.05). In terms of pelvic floor function, patients of both groups showed significant improvement at 3 months and 6 months after surgery (P < 0.05). In terms of quality of life, the two groups exhibited significant improvement at 6 months after surgery (P < 0.05). PFIQ-7, PFDI-20, and UDI-6P of the observational group were lower than those of the control group, while PISQ-12 was higher than that of the control group but all with no significant difference (P > 0.005). In addition, the total complication rate of the observation group was 2.27% (1/44), which was significantly lower than 22.73% (10/44) of the control group (P < 0.05). Conclusion New-style APVR-modified ISFF can effectively treat POP and improve the quality of life of such patients, with less postoperative complications and high safety.